Figurations of Homeland: Fatherland, Nation, Republic (2014)
This article looks for an answer to the question about the specificity of the bond that the concept of nation expresses. In order to achieve this goal, the texts of the so-called first voices of nationalism in the 18th and 19th centuries, as well as recen